2017
DOI: 10.4103/jehp.jehp_37_17
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of nursing and midwifery students regarding the role of the hidden curriculum in patient education: A qualitative study

Abstract: BACKGROUND:Although education is one of the most substantial needs of patients that should be taught by nurses and midwives, it is not clearly defined through the hidden curriculum in students’ teaching programs. The aim of this study was to explore the patient education through the hidden curriculum in the perspectives of nursing and midwifery students.MATERIALS AND METHODS:A qualitative, content analysis study was performed and twenty nursing and midwifery students were interviewed. Data were collected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…Consistent with previous studies, communication with patients should be based on the demographic characteristics of the clients and not everyone should receive the same treatment (9,12). According to previous qualitative and quantitative studies, interventions are needed at multiple levels to address social and economic barriers (10,(13)(14)(15). The most effective intervention currently receiving particular attention in Iran's Health Care System is the education of indigenous forces for providing health services, because the health care providers are most similar to those in the region where health education services are provided in terms of socioeconomic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with previous studies, communication with patients should be based on the demographic characteristics of the clients and not everyone should receive the same treatment (9,12). According to previous qualitative and quantitative studies, interventions are needed at multiple levels to address social and economic barriers (10,(13)(14)(15). The most effective intervention currently receiving particular attention in Iran's Health Care System is the education of indigenous forces for providing health services, because the health care providers are most similar to those in the region where health education services are provided in terms of socioeconomic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Interest has an undeniable effect on the effort to improve health education services and becoming professional in this field. Interest in the academic field of study is one of the important and influential factors in becoming a professional in education and the formation of a professional commitment (14,18). A study on the barriers to achieving professional ethics showed that inappropriate attitude toward the aca-demic discipline leads to lack of motivation and interest (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In nursing, peer learning can mean that two students at the same (or different) academic level, plan, carry out and evaluate nursing care together, under supervision. 7 This model places more of the responsibility to achieve a successful clinical learning on the students than on the preceptors, 6 since students are expected to actively participate as equals in reasoning about nursing and clinical learning. 8 The accumulated knowledge suggests that students in peer learning gain greater confidence and independence in learning, acquire a higher level of personal and professional skills including empathy, communication, organization, leadership, decision-making, and teamwork skills compared with students supervised along traditional lines.…”
Section: Introductionmentioning
confidence: 99%